Reporting of Randomized Controlled Trials in Cleft Lip and Palate: A 10-Year Review. (March 2017) - Hardwicke, Joseph; Nassimizadeh, Mohammad; Richard, Bruce
Objectives: Reviews of the quality of reporting of randomized controlled trials (RCTs) have recently been conducted in different surgical specialties. In this review of RCTs relating to cleft lip, cleft palate, and cleft lip and palate (CL/P), we investigate the quality of reporting against the Consolidated Standards of Reporting Trials (CONSORT) checklist. Design: A systematic review of CL/P RCTs published from 2004 to 2013, with the included articles scored against the CONSORT checklist. Patients, Participants: The literature search identified 174 articles. Studies were selected for participants with CL/P who were involved in an RCT with prospective data collection and reported in a full journal article. A total of 6352 participants were included from 65 CUP RCTs during the study period. Main Outcome Measures: The methodological quality of RCTs was assessed using the CONSORT checklist and Jadad scale. Results: The mean CONSORT score was 15.8, and the mean Jadad score was 3.3. There was a significant positive correlation between the CONSORT and Jadad score ( P < .0001, ρ = .47). The only significant correlation showed that with an increasing number of authors, both the CONSORT and the Jadad score increased. Conclusion: This analysis has shown that that there are deficiencies in the transparent reporting of factors such as randomization implementation, blinding, and participant flow. Interventions, outcomes, and the interpretation of results are well presented. We would recommend that RCTs are conceived and undertaken using the CONSORT checklist and reported in a clear and reproducible manner.